2008
DOI: 10.1080/03639040801929075
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Novel Polyester-Ibuprofen Conjugates for Modified Drug Release

Abstract: Ibuprofen was conjugated at different levels to a novel polyester, poly(glycerol-adipate-co-ω-pentadecalactone) (PGA-co-PL), via an ester linkage to form a prodrug. The conjugates were characterized by differential scanning calorimetry (DSC), nuclear magnetic resonance (NMR), infrared (IR), gel permeation chromatography (GPC), ultraviolet (UV), and high-performance liquid chromatography (HPLC). The conjugates had a molecular weight between 18 and 24 kDa, and there was a suppression of the free hydroxyl groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 18 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…The lack of monomer present in the reaction mixture was confirmed by NMR and IR spectroscopies. Chloroform was chosen because it is the preferred solvent to terminate the lipase reactions; despite the use of this solvent in this one step, our overall synthetic methods are greener than traditional methods; other methods to achieve similar reactions utilize excess carbodiimides, chlorinated solvents, and metal catalysts often used in contrast to solvent‐free, catalytic reactions, safer solvents, and enzyme catalyst. GPC analysis indicated that M w values were moderate and PDI values narrow (Table ) substantiating that an additional purification step was unnecessary.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of monomer present in the reaction mixture was confirmed by NMR and IR spectroscopies. Chloroform was chosen because it is the preferred solvent to terminate the lipase reactions; despite the use of this solvent in this one step, our overall synthetic methods are greener than traditional methods; other methods to achieve similar reactions utilize excess carbodiimides, chlorinated solvents, and metal catalysts often used in contrast to solvent‐free, catalytic reactions, safer solvents, and enzyme catalyst. GPC analysis indicated that M w values were moderate and PDI values narrow (Table ) substantiating that an additional purification step was unnecessary.…”
Section: Resultsmentioning
confidence: 99%
“…In systems where the drug is chemically incorporated into the polymer, non‐biodegradable polymers are often used, leading to potential adverse effects when used in vivo as the polymer may remain . In previous work, an ibuprofen‐containing polyester was prepared using N435 but had low drug loading (3–13%) and a burst release; 35% of ibuprofen was released after 18 d, but not thereafter . Polymers of sebacic acid, glycerol, poly(ethylene glycol), and ketoprofen have similarly been developed using N435; however, low drug loading (<25%) and the use of toxic, expensive vinyl moieties remain issues.…”
Section: Introductionmentioning
confidence: 99%
“…A novel therapeutic approach of OA consists of using intra-articular drug delivery systems (DDSs) with the ability to locally release NSAIDs 17 . Various formulations of DDS are currently investigated to achieve a sustained release of NSAIDs [18][19][20] . Intra-articular DDS should provide long-term sustained release of NSAIDs and diminish the amount of systemic drug exposition, which in turn reduces the relatedadverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, this has been demonstrated through functionalisation of PGA with N-acyl amino acids via Steglich Esterification [8]. Additionally, the drug molecules indomethacin [11], methotrexate [12] and ibuprofen [13] have been successfully coupled to the polymer backbone. The low toxicity of PGA coupled with the ease with which it can be synthesised, functionalised with drug molecules and formulated into nanoparticles means it shows great potential as a polymeric platform for both targeted and systemic drug delivery.…”
Section: Introductionmentioning
confidence: 99%